Impacts of the monetary policy on the exchange rate: case study of Vietnam - Pham, Van Anh (University of Economics Ho Chi Minh City, 2023)
Purpose The purpose of this paper is to evaluate and analyze impacts of the monetary policy (MP) – money aggregate and interest rate – on the exchange rate in Vietnam. Design/methodology/approach The study uses data over the period of 2008–2018 and applies the vector autoregression model, namely recursive restriction and sign restriction approaches. Findings The main empirical findings are as follows: a contraction of the money aggregate significantly leads to the real effective exchange rate (REER) depreciating and then appreciating; a tightening of the interest rate immediately causes the REER appreciating and then depreciating; and both the money aggregate and the interest rate strongly determine fluctuations of the REER. Originality/value The quantitative results imply that the MP affects the REER considerably.